Report on the Federal Court of Canada and the Tax Court of Canada - Canada Office of the Auditor General (The Office, 1997)
This report presents the findings and recommendations from our examination of the possible regionalization and/or merger of the Federal Court of Canada Trial Division and the Tax Court of Canada Trial Division and the Tax Court of Canada and consolidation of their administrative support services. The examination was conducted in accordance with the Auditor General Act pursuant to an order-in-council recommended by the Minister of Justice. The report also presents the results of our audit of the registry services of the two courts. The scope of our review and the approach we used are described in Section 1. A copy of the order-in-council is attached as Appendix 1.